Perceptions of Disability among University Students - Saadun, Saadiah Juliana; Abdullah, Mohd Zulkifli; Mohamed Besir, Mohammad Shahril; Jamal, Aziz; Mat Hasan, Noor Zaihan; Nordin, Nor Azzura; Imran Nanang, Jazmin Qistina (Information Management and Business Review, 2023)
Perceptions of disability are important constructs that influence not only the well-being of people with disabilities but also the moral compass of society. Negative attitudes toward disability can lead to social exclusion and isolation of people with disabilities, whereas positive attitudes promote social inclusion. The present study was conducted to examine the main predictors of disability perceptions among university students, provided that understanding these factors can help develop effective interventions to improve students’ attitudes toward peers with disabilities and reduce intergroup prejudice. Using 110 responses from university students at a public university, the study found that knowledge and exposure contribute significantly to perceptions among university students. Management of the university plays a critical role in shaping positive perceptions by facilitating meaningful interactions with people with disabilities, promoting disability awareness and education, and creating an environment that values diversity.